HPLC Analysis and In-vitro Dissolution studies of fifteen brands of Diclofenac tablets sampled from Pharmacy stores within the Mainland area of Lagos state, Nigeria - Adeyemi, David K.; Johnson, Oluwatosin O.; Oluwaseun, Oluwabamiwo E. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2017)
The present study aimed at analysis and in vitro dissolution studies of Diclofenac tablets sampled from Pharmacy stores within the Mainland area of Lagos state, Nigeria. Qualitative and quantitative parameters using visual inspection, uniformity of weight, uniformity of drug content and dissolution test were employed. High performance liquid chromatography (HPLC) method was used to analyze the amount of Diclofenac in the samples. Visual inspections of (fifteen different brands) individual tablets showed no visible physical deterioration, capping or breakage and all the samples were appropriately labelled and packaged. The Percentage content of the different Diclofenac tablets analysed was within 4.58% to 182.04%, where only two samples (13.33%) passed the USP specified range of 90 – 110%. The dissolution rates at pH 1.2 both with and without pepsin ranged from 4.0-10.0 %. At pH 6.8, there was a marked increase in dissolution (24%-134%) indicating the increase in drug release at higher pH. Only 2 of the six drugs assayed for dissolution with percent release of 63.81% and 71.76% complied with the official monograph specification that 56% -76% of the drug must be released at pH 6.8 in 4 hours. The results of this study indicate the need for periodic assessment of pharmaceutical products that are commercially available in the country.